STABILIZATION OF ACTIVE SLUDGE AFTER WASTEWATER TREATMENT CONTAMINATED BY PETROLEUM PRODUCTS - Semenova, Olena; Reshetnyak, Lyudmila; Bublienko, Natalia; Smirnova, Jelizaveta; Shylofost, Tatyana (Proceedings of National Aviation University (archive), 2016)
Purpose: Biochemical purification of wastewater containing refined petroleum products takes place due to the oxidation of pollutants by active sludge organisms. As a result of this process the intense consumption of pollutants by active sludge and its growth occurs. Therefore, the possibility to use active sludge containing refined petroleum products after wastewater treatment requires its stabilization. Methods: In this work the oxidation by a 30% hydrogen peroxide solution was studied for its use as a stabilizer. Chemical oxidizers, including hydrogen peroxide destroy organic polymers retaining free water thus promoting water release from the structure of sludge particles. On the other hand remains of fine structured oxidized biopolymers can lead to filter clogging, that is, reduce moisture exchange of sludge. Results: The experiment was carried out to find out the correlation between the doses of hydrogen peroxide and the resistivity value of sludge filtration. Discussion: Stabilized active sludge can be used as a fuel for boiler rooms, which in its turn will reduce natural gas consumption for the enterprise needs.